Analisis Pengaruh Budaya Sekolah Terhadap Karakteristik Peserta Didik (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the influence of school culture on student characteristics. School culture includes values, norms, habits, and practices that are carried out by all school residents, including principals, teachers, staff, and students. The characteristics of the students in question include cognitive, affective, and psychomotor aspects that reflect their academic, emotional, and social development. This research was carried out qualitatively with a descriptive approach. The subject of the research is junior high school students and the object of the research investigated is an effort to find out the influence of school culture on the characteristics of students. The data collection techniques used are questionnaires, interviews. Data analysis techniques are data reduction, data presentation and verification (drawing conclusions). The results of the study showed that the overall score of the questionnaire results that had been distributed to the respondents was 20 respondents, with 13 questionnaire questions so that the result or overall score was 1,325. As for the influence of school culture on student characteristics, which is 60% - 79.99% (agree, like or like), it can be said that school culture has a positive influence on students